MAKING BRAZILIAN SPINACH CHIPS TO DEVELOP ENTREPRENEURIAL SPIRIT THROUGH LEARNING STRENGTHENING PROJECT PANCASILA STUDENT PROFILE IN EARLY CHILDHOOD EDUCATION - Zahra, Lina Kamalia; Monica Arningsari; Sumarno (Schola, 2024)
Study This aiming for see impact from making chips Brazilian spinach as a learning medium project strengthening profile student Pancasila, in particular in grow soul entrepreneurship in children age early. Through activity production chips Brazilian spinach, children involved active in all over stages production, start from stage preparation material until marketing product end. Population study totaling 42 children in Early Childhood Education in Kebumen. The research method used is method qualitative where the data is collected through observation, and documentation. Research results show that activity making chips Brazilian spinach can become an effective learning medium for grow soul entrepreneurship in children age early.